Cosmogenic ages indicate no MIS 2 refugia in the Alexander Archipelago, Alaska - C. K. Walcott; J. P. Briner; J. F. Baichtal; A. J. Lesnek; J. M. Licciardi (Geochronology, 2022)
The late-Pleistocene history of the coastal Cordilleran Ice Sheet remains relatively unstudied compared to chronologies of the Laurentide Ice Sheet. Yet accurate reconstructions of Cordilleran Ice Sheet extent and the timing of ice retreat along the Pacific Coast are essential for paleoclimate modeling, assessing meltwater contribution to the North Pacific, and determining the availability of ice-free land along the coastal Cordilleran Ice Sheet margin for human migration from Beringia into the rest of the Americas. To improve the chronology of Cordilleran Ice Sheet history in the Alexander Archipelago, Alaska, we applied 10 Be and 36 Cl dating to boulders and glacially sculpted bedrock in areas previously hypothesized to have remained ice-free throughout the local Last Glacial Maximum (LLGM; 20–17 ka). Results indicate that these sites, and more generally the coastal northern Alexander Archipelago, became ice-free by 15.1 ± 0.9 ka ( n = 12 boulders; 1 SD). We also provide further age constraints on deglaciation along the southern Alexander Archipelago and combine our new ages with data from two previous studies. We determine that ice retreated from the outer coast of the southern Alexander Archipelago at 16.3 ± 0.8 ka ( n = 14 boulders; 1 SD). These results collectively indicate that areas above modern sea level that were previously mapped as glacial refugia were covered by ice during the LLGM until between ∼ 16.3 and 15.1 ka. As no evidence was found for ice-free land during the LLGM, our results suggest that previous ice-sheet reconstructions underestimate the regional maximum Cordilleran Ice Sheet extent, and that all ice likely terminated on the continental shelf. Future work should investigate whether presently submerged areas of the continental shelf were ice-free.